ANALISA SOSIAL EKONOMI PEMBANGUNAN PUSAT PERBELANJAAN MODERN; STUDI KASUS PEMBANGUNAN LOTTE MALL DI KECAMATAN PONDOK AREN, TANGERANG SELATAN 2010 - Yusa' Farchan (Jurnal Renaissance, 2016)
In modern civilization, the existence of modern shopping centers often become a symbol of the progress of a city. This study aimed to analyze the social and economic development plans Lotte Mall in District Pondok Aren, Tangerang Selatan. This study uses a qualitative method of collecting data through observation and indepth interview. Lotte Mall development is not only a positive impact, but also had a negative impact. The positive effect is; First, Lotte Mall provides nearly half of the needs of human life. Consumers or visitors can easily select and purchase the desired item. Second, the existence of Lotte Mall can drive the economy of local communities. Third, the construction of Lotte Mall will obviously create employment so that it can push the unemployment rate although in certain scale. Fourth, the existence of Lotte Mall has become a prerequisite for modern urban civilization. The establishment of Lotte Mall will certainly attract investment for development in other sectors such as property and other businesses. As for the negative impact of the construction of Lotte Mall, among others; First, a potentially lethal retailer small or medium class because it is not able to compete with large classes of retail traders. Second, the existence of Lotte Mall promoting wider logic of consumerism because people tend to be "spoiled" with ease and facility of shopping easy and convenient. Thirdly, the presence of Lotte Mall tends to turn off the traditional markets that already exist in the vicinity of the shopping center. Fourth, further reducing green open spaces as public spaces are natural and pro-environment. The existence of Lotte Mall also has the potential to cause traffic congestion due to be sentrum vehicular traffic.Keywords: socio-economic impacts of development mall; modern city; partnerships traditional markets and micro